THE EFFECT OF REINFORCEMENT ON STUDENTS' LEARNING ACHIEVEMENT IN THE FIELD OF ISLAMIC STUDIES AT SMP NEGERI 34 MAKASSAR - M. Makbul; Ferianto Ferianto (Universitas Islam Negeri Sumatera Utara Medan, 2022)
This article discusses the Effect of Reinforcement on Students' Learning Achievement in the Field of Islamic Studies at SMP Negeri 34 Makassar